1998
DOI: 10.1177/1354067x9800400302
|View full text |Cite
|
Sign up to set email alerts
|

Social Representations and beyond: Brute Facts, Symbolic Coping and Domesticated Worlds

Abstract: Social representation theory is scrutinized for its capacity to ask new questions and to give new answers to social psychological problems. Its social constructionist implications and relationship to brute facts are investigated. It is shown that social representations result from collective symbolic coping with 'brute' facts. Consequently representations create the domesticated world of social objects which implies considering activity as part of a representation. Culture change in modern societies is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
0
26

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 23 publications
1
133
0
26
Order By: Relevance
“…Por representação social, define-se a elaboração de um objeto social pela comunidade com o propósito de comunicar e agir (Moscovici, 1963;Wagner, 1998). Contudo, para que esse objeto se diferencie e possa se caracterizar como uma representação social, ele deve estar implicado com os valores partilhados com os outros que se concretizam na pertença a uma dada cultura (Jovchelovitch, 2008).…”
Section: Os Usos Sociais Do Crackunclassified
See 1 more Smart Citation
“…Por representação social, define-se a elaboração de um objeto social pela comunidade com o propósito de comunicar e agir (Moscovici, 1963;Wagner, 1998). Contudo, para que esse objeto se diferencie e possa se caracterizar como uma representação social, ele deve estar implicado com os valores partilhados com os outros que se concretizam na pertença a uma dada cultura (Jovchelovitch, 2008).…”
Section: Os Usos Sociais Do Crackunclassified
“…Assim, um objeto social é qualquer entidade material, imaginária ou simbólica que as pessoas nomeiam, atribuindo características e valores e, consequentemente, tornando-se aptas a falar sobre ele, sendo sempre um objeto para um grupo, sociedade ou cultura (Wagner, 1998). As representações são modos específicos de compreender, comunicar e criar a realidade, importantes porque orientam a forma de nomear e definir conjuntamente os diferentes aspectos da realidade cotidiana, interpretando-os e possibilitando tomar decisões e posicionar-se diante destes (Jodelet, 2001).…”
Section: Os Usos Sociais Do Crackunclassified
“…However, mass media communications are underpinned by representational systems, and because the producers and the receivers reside within the same historicity, both the producers and receivers construct and receive media communications (Rouquette 1996, Moloney 2007. These shared representations are situated between stasis and transition; they are dynamic and malleable, making them susceptible to influence by those who have the agency and resources to proliferate one version of events over others (Jovchelovitch 1997, Wagner 1998, Moloney 2007). …”
Section: Social Representations Theorymentioning
confidence: 99%
“…Recent SRT commentators have suggested that the strong constructionism and relativism of discursive psychology is self refuting and allows no possibility for political commitment (Wagner, 1998;Moscovici & Markova, 1998). There is not space to tackle these points in full here.…”
Section: Social Representations or Discursive Psychologymentioning
confidence: 99%